Inversión pública y desarrollo local según los trabajadores de la municipalidad distrital de Simón Bolívar, Pasco 2022 - Bazan Vicente, Rodolfo (2024)
Inversión pública y desarrollo local según los trabajadores de la municipalidad distrital de Simón Bolívar, Pasco 2022